Peningkatan Pengetahuan Petani Kopi Cibulao mengenai Pencegahan Helminthiasis yang Ditularkan melalui Tanah karena Pupuk Hewan - Siagian, Tetty Barunawati; Dahliani, Lili; Azhar, Aidil; Siagian, Gary Yeffta Herbeth (Institut Pertanian Bogor, 2024)
Animal fertilizer comes from animal waste and has undergone a decomposition process. The use of animal fertilizer has a potential risk to farmers' health if they do not heed Occupational Health and Safety (K3) standards for the personal safety of coffee farmers. The impact is that coffee farmers can be infected with worms transmitted through the soil (Soil Transmitted Helminth). This community service activity aims to increase the knowledge of Cibulao coffee farmers about preventing Soil-Transmitted Helminth worm infections in the application of animal fertilizer through counselling and technical guidance. The community service partners are the Cibulao coffee farmer group. The methods used are counselling, technical guidance and evaluation. The number of participants who attended this technical guidance was 17 coffee farmers. The training occurred in Telaga Saat Village, Cisarua District, Bogor Regency. The results of this community service activity show that there has been an increase in understanding of measures to prevent STH infection when using animal fertilizer. This increase can be seen from the pre-test and post-test results carried out before and after providing the material and technical guidance. The success of this program can be seen in farmers who are skilled in applying animal fertilizer using K3 and the desire for sustainable technical guidance regarding the maintenance and health care of goats and sheep.